PERFORMANCE AND HOTELS WASTE MANAGEMENT STRATEGIES IN TOURISM REGION OF UBUD BALI - I Wayan Adiputra Gunawan; Made Sudiana Mahendra; I Wayan Diara (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2018)
ABSTRACT PERFORMANCE AND HOTELS WASTE MANAGEMENT STRATEGIES IN TOURISM REGION OF UBUD BALI The aim of this research was to know performance and formulate waste management strategies by star hotels in Ubud Tourism Region. Based on the result of the research, there were 2 hotels (14,28%) with very good classification, 6 hotel (42,86%) with good classification, 3 hotel (21,43%) with moderate classification and 3 hotels (21.43%) with poor classification. The strategy formulated to improve the effectiveness of hotels waste management especially for those for moderate and poor was by conducting analysis of internal factors (IFAS) and external factors (EFAS) which then analyzed with SWOT matrix. Based on the result of SWOT analysis using balance score card, it was found that the star hotel waste management condition which was in moderate category and poor was in quadrant III. This condition indicated that the strategy formulated in the combination of weakneas and opportunities. The formulation of strategy based on SWOT Analysis matrix were as follows: (1) Developing SOP of waste management by referring to the legislation in the environmental; (2) Improving and adding components of waste treatment facilities (WWTP, chimneys, and hazardous waste storage to meet technical standards; (3) Socializing waste management policy to all hotel employees; (4) Apply to the government waste management training for staff / human resources engineering division; and (5) Reporting the performance of the waste management system to the Gianyar Regency Environmental Office every 3 months. Keywords : Performance; Waste, Management Strategy, IFAS, EFAS, and SWOT Analysis